Optimalisasi Membaca Permulaan Siswa Kelas II SD Inpres Ndindibung Melalui Penggunaan Media Kartu Gambar–Kata Kontekstual - Nuhera Nuhera; Pamela Mikaresti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This classroom action research aims to improve the early reading skills of second-grade students at SD Inpres Ndindibung through the use of picture–word card media. The study involved 22 students as research subjects and was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research instruments included an engagement observation sheet, a decoding error checklist (substitution, omission, inversion), and a reading test measuring accuracy, speed (words per minute/WPM), and literal comprehension.The findings revealed an increase in learning mastery from 45% (pre-action) to 77% (Cycle I) and 91% (Cycle II). Reading speed improved from 39 WPM to 63 WPM, while accuracy rose from 62.8% to 83.4%. These results indicate that the use of picture–word cards strengthens grapheme–phoneme connections and enriches contextual vocabulary, making it effective in enhancing students’ reading fluency. The findings highlight the importance of explicit phonics instruction, guided repeated reading, and visual supports in developing early reading abilities.